Akaline, saline and mixed saline-alkaline stresses induce physiological and morfo-anatomical changes in Lotus tenuis shoots - Paz, Rosalía (2014)
Saline, alkaline and mixed saline–alkaline conditions frequently co‐occur in soil. In this work, we compared these plant stress sources on the legume Lotus tenuis, regarding their effects on shoot growth and leaf and stem anatomy. In addition, we aimed to gain insight on the plant physiological status of stressed plants. We performed pot experiments with four treatments: control without salt (pH = 5.8; EC = 1.2 dS·m−1) and three stress conditions, saline (100 mm NaCl, pH = 5.8; EC = 11.0 dS·m−1), alkaline (10 mm NaHCO3, pH = 8.0, EC = 1.9 dS·m−1) and mixed salt–alkaline (10 mm NaHCO3 + 100 mm NaCl, pH = 8.0, EC = 11.0 dS·m−1). Neutral and alkaline salts produced a similar level of growth inhibition on L. tenuis shoots, whereas their mixture exacerbated their detrimental effects. Our results showed that none of the analysed morpho‐anatomical parameters categorically differentiated one stress from the other. However, NaCl‐ and NaHCO3‐derived stress could be discriminated to different extents and/or directions of changes in some of the anatomical traits. For example, alkalinity led to increased stomatal opening, unlike NaCl‐treated plants, where a reduction in stomatal aperture was observed. Similarly, plants from the mixed saline–alkaline treatment characteristically lacked palisade mesophyll in their leaves. The stem cross‐section and vessel areas, as well as the number of vascular bundles in the sectioned stem were reduced in all treatments. A rise in the number of vessel elements in the xylem was recorded in NaCl‐treated plants, but not in those treated exclusively with NaHCO3.